O27 Simulating instant ageing: an innovation to develop interest in health care of later life attachment at the university of nottingham. (5th November 2017) - Mjojo, J; McGowan, T; Blundell, A
Abstract : Background: The projected rising numbers of those aged 65 years and above predicts that the core work for future healthcare professionals will be dominated by caring for older patients with increasing frailty. Anecdotally, fourth year medical students undergoing the Health Care of Later Life module at University of Nottingham indicate caring for frail, older patients is something they have little interest in. This could suggest a disconnection between their existing feelings and the reality of their future work. Evidence shows that frailty is under-recognised in Medical Curriculum¹ and studies show empathy can be improved through experiential learning². We introduced an innovative simulation session entitled "Instant Ageing" to challenge students' attitudes. Methods: At the module induction, students completed 5 tasks and a reflection:- 1. Putting on an "Instant Ageing Gert" suit which simulates the experience of ageing, (joint stiffness, loss of strength and grip, reduced coordination skills, narrowing of visual fields). To gain insight on effects, an activity was done and timed before and whilst wearing the suit. 2. Wearing earplugs to simulate deafness. 3. Putting popcorn kernels in shoes to simulate a painful peripheral neuropathy. 4. Writing a sentence whilst wearing tremor simulating gloves. 5. Wearing a stroke simulation suit, and performing activities such as opening medication bottles. They were encouraged to document prior and current views regarding older patients before and after the session. Results 50 students verbally consented and participated. Questionnaire completion rate was 60%. 66% of those who completed indicated changed views. Themes on attitudes to older patients prior to the session were: "they are too difficult to treat, private, nonspecific, unwilling to divulge information, frustrated and vulnerable". Conclusion: Simulating functional limitations and disabilities while participating in activities of daily life may allow students to appreciate and empathise with older patients. It also helps contextualise Comprehensive Geriatric Assessment by highlighting contributions from doctors, other professionals as well as others. Further work may include asking students to document their views at the end of the attachment so as to evaluate whether the simulation changed their interest or attitudes to older patients. References: . Knight PV, Oliver D, Gordon AL, Turner G. Frailty related aspects of care are under-recognised in UK Curriculum. BMJ 2014: 348g3325. . Oakley R, Pattinson J, Goldberg S, Daunt L, Simra R, Masud T, Gladman JRF, Blundell A, Gordon AL. Equipping tomorrow's doctors for the patient of today. Age and Ageing Volume 2014;43(4):442–447.